1998
DOI: 10.1346/ccmn.1998.0460508
|View full text |Cite
|
Sign up to set email alerts
|

Hard and Soft Acid-Base Model Applied to Bivalent Cation Selectivity on a 2:1 Clay Mineral

Abstract: Abstract--We applied the hard and soft acid-base (HSAB) model Harsh 1990a, 1990b) to bivalent cation exchange on a purified Ca-montmorillonite. As a result, a satisfactory model is proposed to describe the gradual selectivity of exchange with Ca for 4 of the 6 metals studied (Cd, Cu, Pb, Zn). The selectivity is predicted as a function of the differences of electronegativity and softness of the metals. The deviation of Ni and Co data from the predicting model is interpreted in terms of hydration (Ni and Co be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 64 publications
0
17
0
Order By: Relevance
“…The conclusion herein is supported by the comparability between the EXAFS-derived structural parameters of the sorption sample and those of the Cu(NO 3 ) 2 (aq) reference sample (Table 3). In a previous study, Auboiroux et al (1998) have reported that the Vanselow selectivity coefficient for the Cu 2+ /Ca 2+ exchange reaction ($2.42) is clearly higher than that for the Ni 2+ /Ca 2+ exchange reaction ($1.48). In view of this, the Cu(II) ions are expected to more preferentially enter the montmorillonite interlayer compared with the Ni(II) ions.…”
Section: Sorption Behaviors Of Cu(ii) At the Montmorillonite/ Water Imentioning
confidence: 87%
See 1 more Smart Citation
“…The conclusion herein is supported by the comparability between the EXAFS-derived structural parameters of the sorption sample and those of the Cu(NO 3 ) 2 (aq) reference sample (Table 3). In a previous study, Auboiroux et al (1998) have reported that the Vanselow selectivity coefficient for the Cu 2+ /Ca 2+ exchange reaction ($2.42) is clearly higher than that for the Ni 2+ /Ca 2+ exchange reaction ($1.48). In view of this, the Cu(II) ions are expected to more preferentially enter the montmorillonite interlayer compared with the Ni(II) ions.…”
Section: Sorption Behaviors Of Cu(ii) At the Montmorillonite/ Water Imentioning
confidence: 87%
“…9A). The Vanselow selectivity coefficient for the Ni 2+ /Ca 2+ exchange reaction ($1.48) is reported to be lower than that for the Cu 2+ /Ca 2+ exchange reaction ($2.42) (Auboiroux et al, 1998). Hence, the exchange reaction between Ni(II) ions and the exchangeable Na + ions is inhibited by the coexisting Cu(II) ions.…”
Section: Sorption Behaviors Of Ni(ii) At the Montmorillonite/water Inmentioning
confidence: 93%
“…Electronegativity values shown in Table 4 cannot explain the order of affinity for metal ions shown by COSAC, as it has been reported that metals with higher electro-negativity show higher adsorption yields (Li et al 2003;Lima et al 2007). Based on the hard soft acid-base (HSAB) theory or Pearson acid-base concept (Auboiroux et al 1998;Padilla-Ortega et al 2013), Cu(II) and Ni(II) For all the above considerations, it is evident that the affinity order Cd(II) [ Ni(II) [ Cu(II) found in this work for the studied metal ions cannot be related to the physicochemical properties of metal cations. Physicochemical properties of metal ions coupled with the steric effects of the adsorbent and physicochemical properties of its surface open the way to a multitude of interpretations that can be contradictory or even confusing.…”
Section: Equilibrium Adsorption Isotherms Of Monosolute Systemsmentioning
confidence: 83%
“…While zeolites are multicomponent catalysts with the aluminosilicate matrix, pillared clays are practically an expanded form of smectites formed by an introduction of a large interlayer cation [7,8]. Many researchers, however, are going back to basics by working with traditional clays to get a better understanding of the catalytic mechanism and substance selectivity [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Another significant application is of great interest in environmental and soil science [9]. In this respect, clay minerals may fix metals through ion exchange [13,14] or surface complexation [15].…”
Section: Introductionmentioning
confidence: 99%